The Eloquent Blood: The Goddess Babalon and the Construction of Femininities in Western Esotericism - Hedenborg White, Manon (Oxford Studies in Western Esotericism Ser., 2019)
The Eloquent Blood focuses on the changing construction of femininity and feminine sexuality in interpretations of the goddess Babalon. A central deity in Thelema, the religion founded by the notorious British occultist Aleister Crowley (1875-1947), Babalon is based on Crowley's favorable reinterpretation of the biblical Whore of Babylon, and is associated with liberated female sexuality and the spiritual ideal of passionate union with existence. Combining research on historical and contemporary Western esotericism with feminist and queer theory, the book sheds light on the ways in which esoteric movements and systems of thought have developed over time in relation to political movements.